A Bioweapon or a Hoax? The Link Between Distinct Conspiracy Beliefs About the Coronavirus Disease (COVID-19) Outbreak and Pandemic Behavior. Issue 8 (November 2020) - Imhoff, Roland; Lamberty, Pia
During the coronavirus disease pandemic rising in 2020, governments and nongovernmental organizations across the globe have taken great efforts to curb the infection rate by promoting or legally prescribing behavior that can reduce the spread of the virus. At the same time, this pandemic has given rise to speculations and conspiracy theories. Conspiracy worldviews have been connected to refusal to trust science, the biomedical model of disease, and legal means of political engagement in previous research. In three studies from the United States ( N = 220; N = 288) and the UK ( N = 298), we went beyond this focus on a general conspiracy worldview and tested the idea that different forms of conspiracy beliefs despite being positively correlated have distinct behavioral implications. Whereas conspiracy beliefs describing the pandemic as a hoax were more strongly associated with reduced containment-related behavior, conspiracy beliefs about sinister forces purposefully creating the virus related to an increase in self-centered prepping behavior.